Exiting Capitalist Globalisation: Westra's Unoist Approach. Issue 2 (15th March 2017) - Bell, John R.
ABSTRACT: Published in 2015, Richard Westra's Exit from Globalization employs a variation of Kozo Uno's levels of analysis approach to the comprehension of economic life under capitalism and beyond. The approach has three elements. First, a dialectical pure theory that simultaneously exposes both the logic that capital and its impersonal society-wide competitive market employed in its largely successful attempt to regulate and reproduce material/substantive/real economic life and capital-labour relations during liberal capitalism and the economic norms that all historical societies must observe by whatever means so as to continue to reproduce material economic life. Second, a stages theory (mercantilism, liberalism and capitalist imperialism) of capitalism's historical development. Finally, empirical studies of aspects of historical capitalism, informed by the pure and stages theories and a knowledge of general economic norms, may be conducted. Following Albritton, Westra advances a theory of a final fourth stage of capitalism that Uno, who died in 1977, never contemplated. He theorises the ongoing disintegration of consumerism and capitalism itself in the present era. In fleshing out a model advanced by Sekine, Westra theorises the functioning of a vibrantly democratic, partially relocalised eco-socialism.